THE SOCIAL DISCRIMINATION AGAINST FORMER TERRORIST CONVICTS AND THEIR FAMILIES: Psychological Perspectives (JOURNAL OF INDONESIAN ISLAM, 2014)
This study examines the social discrimination against the former terrorist convicts and their families.  It is aimed at knowing about former terrorist convicts’ family patterns of community interaction, the growing social discrimination within the social life of former terrorist’s convicts’ family, the impact of social discrimination against the family of former terrorist convicts, and the coping behavior of former terrorist convicts over that situation. This study uses descriptive qualitative research methods. The study finds that the pattern of interactions between the family of former terrorist convicts and their surrounding communities can be divided into two phases, before and after the arrest. It also maintains that the social discrimination against the family of former terrorist convicts occurs when they are dealing with people outside the village of Tenggulun, in the form of isolation, token and reserve discrimination. The prejudice and social discrimination on the family of former terrorist convicts impact on their self-worth, self-esteem and well being. Coping behavior by former terrorist convicts and their families are two kinds, namely emotion focused coping and problem-focused coping.